Kepercayaan dan Kepuasan Penggunaan LMS Mahasiswa Selama Pembelajaran Daring - Teguh Prasetyo; Arita Marini; Mohamad Syarif Sumantri (Jurnal Penjaminan Mutu, 2021)
The implementation of online learning through the Learning Management System (LMS) is universal in higher education. The presentation of learning at the LMS is expected to facilitate student learning during the Covid-19 pandemic. This aims of research to determine the effect of belief in the use of LMS on learning satisfaction in LMS carried out by students. The research approach uses a quantitative type of correlation. This study used a research sample of 101 students. The research instrument is an online questionnaire that has been tested for validity and reliability and is analyzing by regression. The results showed that the regression formulation was: Y = 1.535 + 0.706. Is the influence of the belief variable using LMS significant on LMS learning satisfaction? Result of the regression analysis, the significance value of 0.000 is smaller than 0.05, it can be concluded that belief in the use of LMS affects LMS learning satisfaction. How much trust do the beliefs of LMS affect learning satisfaction at the LMS (r-square), namely 55.8%, while the remaining 44.2% is another variable and is not researched?. Belief in using LMS on learning satisfaction in LMS is based on aspects of content quality, learning success, ease, and behavior.